LEARNING STYLES OF FIRST SEMESTER EFL STUDENTS AT UNIROW TUBAN - Corry Nor Fahmi; Icha Dwi Lestari; Kelvin Wildasyah; Sephia Febriani Carolina; Siti Mahmudah (Universitas PGRI Ronggolawe Tuban, 2023)
This study aimed to investigate the learning styles of first semester EFL students at Unirow Tuban. The questionnaire consisted of 30 questions related to learning styles, which were categorized into three main categories: visual, auditory, and kinesthetic. This study was a type of descriptive with qualitative approach. It was conducted online through Google Form questionnaire. The purpose of the current study is to identify learning style and analyze how it will influence capacity to carry out academic tasks. The participants of this research were 13 students of first semester in PGRI Ronggolawe University Tuban. The findings of the study revealed that the majority of the first semester EFL students at Unirow Tuban had a preference for visual and auditory learning styles, while a smaller proportion of students had a preference for kinesthetic learning styles. Furthermore, the study found that there were significant differences in learning styles preferences between male and female students and also because they come from different region that created diversities. Overall, the results of this study provide valuable insights into the learning styles of first semester EFL students at Unirow Tuban, which can help educators design and implement effective teaching strategies to cater to students' preferred learning styles and enhance their learning outcomes.